Uji Kuat Tekan dan Kuat Lentur Beton Akibat Reduksi Semen Dengan Campuran Abu Sekam Padi Dan Bentonite - Chau, Jaycin Agnes Elisa; Yusuf, A. Rumpang; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The rapid development of concrete technology has introduced additives that enhance and improve concrete properties. One material that can substitute cement is pozzolan, such as rice husk ash (RHA) and bentonite, which contain SiO2 and Al2O3. This study aims to examine the effect of RHA and bentonite mixtures as partial cement replacements on the compressive and flexural strength of concrete. The cement content was reduced by 5%, 10%, and 15%, and replaced with RHA and bentonite in proportions of (0%:100%), (100%:0%), and (50%:50%) for a 5% reduction, and (50%:50%) for 10% and 15% reductions. The results showed that normal concrete achieved a compressive strength of 25.29 MPa, while RHA 5% yielded 18.40 MPa, BT 5% achieved 24.44 MPa, and RHA 2.5% BT 2.5%, RHA 5% BT 5%, and RHA 7.5% BT 7.5% produced strengths of 22.27 MPa, 16.28 MPa, and 10.38 MPa, respectively. The normal concrete flexural strength was 3.73 MPa, with the optimum flexural results for RHA 5% at 4.00 MPa, BT 5% at 4.27 MPa, and the RHA 5%, BT 5% mix at 3.87 MPa.